2017
DOI: 10.1155/2017/4082938
|View full text |Cite
|
Sign up to set email alerts
|

Bacteraemia in Intensive Care Unit: Clinical, Bacteriological, and Prognostic Prospective Study

Abstract: Objectives. We conducted a one-year observational study from December 2012 to November 2013 to describe the epidemiology of bacteraemia in intensive care units (ICU) of Mohammed V Military Teaching Hospital of Rabat (Morocco). Methods. The study consisted of monitoring all blood cultures coming from intensive care units and studying the bacteriological profile of positive blood cultures as well as their clinical significance. Results. During this period, a total of 46 episodes of bacteraemia occurred, which co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
14
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 24 publications
12
14
2
1
Order By: Relevance
“…Ibrahim observed in 2018 that 81% of the isolates were Gram-negative, and male patients (59.7%) were predominant in that study [9]. The predominance of Gram-negative isolates in older male patients admitted to ICUs has been observed in studies conducted by Bianco et al, Sligl et al, and Lachhab et al [19][20][21]. Males are generally more prone to infections than females, due to differences in the sex steroids as well as imbalance of sex-chromosomelinked genes [22].…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Ibrahim observed in 2018 that 81% of the isolates were Gram-negative, and male patients (59.7%) were predominant in that study [9]. The predominance of Gram-negative isolates in older male patients admitted to ICUs has been observed in studies conducted by Bianco et al, Sligl et al, and Lachhab et al [19][20][21]. Males are generally more prone to infections than females, due to differences in the sex steroids as well as imbalance of sex-chromosomelinked genes [22].…”
Section: Discussionmentioning
confidence: 72%
“…Males are generally more prone to infections than females, due to differences in the sex steroids as well as imbalance of sex-chromosomelinked genes [22]. The increased incidence in older age groups may be due to their defective defense mechanisms and deteriorating immune systems [21,23].…”
Section: Discussionmentioning
confidence: 99%
“…A study which analyzed bloodstream infections showed that Acinetobacter baumannii was the most commonly encountered Gram negative agent by 23.6%. Incidence of Staphylococcus aureus and Methicillin resistant staphylococcus aureus were 9.1% and 20%, respectively (30). The most commonly determined agents were Acinetobacter baumannii (20.7%) and Klebsiella pneumoniae (19.1%) in our study.…”
Section: Discussionmentioning
confidence: 44%
“…In four of the studies, all needed variables were easily retrieved from the tables, and these studies were included immediately. Crucial characteristics, comments and result are given in Table 1 for these four and the remaining 17 studies that were subjected to the final quality check [3, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44. Six of these 17 studies were included following cross-check of text and tables.…”
Section: Resultsmentioning
confidence: 99%
“…91 ICUs, 28 Hospitals in Egypt.NICU, Paediatric, Medical, Surgical, Neurological2012-14Microbes and susceptibility results given for all types of samples/specimen in one. Not inclued CLSINGNGNGNG-[42]LachhabMoroccoMohammed V Military Teaching HospitalICU2012 - 13 Included NG45255729+[38]MittEstoniaPICU, Tartu University HospitalPICU2004-8 Included CLSI47392311+[43]HorcajadaSpain8 Spanish ICUsUnselected sepsis patients2010-11Author’s clarification about number of Acintobacter isolates. Included CLSI371339131+[33]BartolettiItalyOrsola-Malpighi Hospital Bologna, Italy8874 patients with cirrhosis2008-12Missing test results provided by author.…”
Section: Resultsmentioning
confidence: 99%